Use of national and international growth charts for studying height in European children: development of up-to-date European height-for-age charts - Bonthuis, Marjolein; Schaefer, Franz (PLOS ONE, 2012)
Background Growth charts based on data collected in different populations and time periods are key tools to assess children’s linear growth. We analyzed the impact of geographic factors and the secular trend on height-for-age charts currently used in European populations, developed up-to-date European growth charts, and studied the effect of using different charts in a sample of growth retarded children. Methods and Findings In an international survey we obtained 18 unique national height-for-age charts from 28 European countries and compared them with charts from the World Health Organization (WHO), Euro-Growth reference, and Centers of Disease Control and Prevention (CDC). As an example, we obtained height data from 3,534 children with end-stage renal disease (ESRD) from 13 countries via the ESPN/ERA-EDTA registry, a patient group generally suffering from growth retardation. National growth charts showed a clear secular trend in height (mean height increased on average 0.6 cm/decade) and a North-South height gradient in Europe. For countries without a recent (>1990) national growth chart novel European growth charts were constructed from Northern and Southern European reference populations, reflecting geographic height differences in mean final height of 3.9 cm in boys and 3.8 cm in girls. Mean height SDS of 2- to 17-year-old ESRD patients calculated from recent national or derived European growth charts (−1.91, 95% CI: −1.97 to −1.85) was significantly lower than when using CDC or WHO growth charts (−1.55, 95% CI: −1.61 to −1.49) (P<0.0001). Conclusion Differences between height-for-age charts may reflect true population differences, but are also strongly affected by the secular trend in height. The choice of reference charts substantially affects the clinical decision whether a child is considered short-for-age. Therefore, we advocate using recent national or European height-for-age charts derived from recent national data when monitoring growth of healthy and diseased European children.
Gesehen am 12.04.2018